2016
DOI: 10.1007/s00277-016-2831-7
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection in patients with haematological diseases and after autologous stem cell transplantation as consolidation: a single-centre study

Abstract: Because of the widespread use of immunosuppressive drugs, CMV infection is one of the most important causes of morbidity and mortality in patients with haematological malignancies worldwide. The aim of the study was to retrospectively analyse the epidemiology of CMV infection in haematological patients. Between 2008 and 2014, 1238 quantitative CMV DNA detections from plasma specimens were performed. These specimens were collected from 271 patients with haematological malignancy. Patients were grouped on the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
0
20
1
2
Order By: Relevance
“…Cytomegalovirus (CMV) infection remains one of the most prevalent opportunistic infections (OI) following solid organ transplantation (SOT), and in individuals with hematologic malignancies or other immunocompromising conditions [1][2][3]. It is associated with significant morbidity due to its direct (CMV disease) and indirect (other OI, rejection, chronic allograft dysfunction) effects [1,2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Cytomegalovirus (CMV) infection remains one of the most prevalent opportunistic infections (OI) following solid organ transplantation (SOT), and in individuals with hematologic malignancies or other immunocompromising conditions [1][2][3]. It is associated with significant morbidity due to its direct (CMV disease) and indirect (other OI, rejection, chronic allograft dysfunction) effects [1,2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, even though CMV reactivation still represents an important complication, most cases are successfully managed with a specific antiviral treatment (often administered within outpatient clinical settings). Still, though rare, CMV end‐organ disease remains a serious life‐threatening event in autografted patients, with an incidence up to 4% as reported throughout the last 20 years, although it is showing a trend toward a significant improvement when considering the more recent studies . Of note, overt CMV disease incidence and mortality appear similar irrespective to the diagnostic strategy adopted, further suggesting the limited usefulness of a prospective monitoring of CMV infection .…”
Section: Cytomegalovirus Infection In Autologous Hematopoietic Stem Cmentioning
confidence: 99%
“…5,[42][43][44][45][46][47][48][49] Even though all these studies showed a significant reactivation rate of CMV infection in patients undergoing ASCT, CMV disease was a rare event, although representing a serious life-threatening risk, with a clinical course and mortality rates similar to those observed after allo-HSCT. 1 3,7,8,39,52,[54][55][56][57][58][59] Of note, overt CMV disease incidence and mortality appear similar irrespective to the diagnostic strategy adopted, further suggesting the limited usefulness of a prospective monitoring of CMV infection. 28 These findings are also in agreement with our recently updated results ( Table 5).…”
Section: Cytomegalovirus Infection In Autologous Hematopoietic Stemmentioning
confidence: 99%
See 1 more Smart Citation
“…Az utóbbi 5 évben megjelent fontosabb tanulmányok szerint a hCMV-infekció a betegek 2,9-33,3%-át érinti, a hCMV-betegség azonban ritka [36]. Hazai adatok szerint rendszeres PCR-monitorozás mellett az autológtranszplantáltak egyharmadában lehet reaktivációt igazolni, ám tüneteket okozó fertőzés csak az érintettek 19%-ában jelentkezett [38,40]. Ha rutinszerű monitorozás, illetve profilaxis nem is indokolt, klinikai gyanú esetén gondolni kell potenciális veszélyes hCMVinfekció lehetőségére is.…”
Section: Hcmv-infekció őSsejt-transzplantációbanunclassified